Variable Signatures of Selection Despite Conserved Recombination Landscapes Early in Speciation. (9th September 2021) - Turbek, Sheela P; Semenov, Georgy A; Enbody, Erik D; Campagna, Leonardo; Taylor, Scott A
Abstract: Recently diverged taxa often exhibit heterogeneous landscapes of genomic differentiation, characterized by regions of elevated differentiation on an otherwise homogeneous background. While divergence peaks are generally interpreted as regions responsible for reproductive isolation, they can also arise due to background selection, selective sweeps unrelated to speciation, and variation in recombination and mutation rates. To investigate the association between patterns of recombination and landscapes of genomic differentiation during the early stages of speciation, we generated fine-scale recombination maps for six southern capuchino seedeaters ( Sporophila ) and two subspecies of White Wagtail ( Motacilla alba ), two recent avian radiations in which divergent selection on pigmentation genes has likely generated peaks of differentiation. We compared these recombination maps to those of Collared ( Ficedula albicollis ) and Pied Flycatchers ( Ficedula hypoleuca ), non-sister taxa characterized by moderate genomic divergence and a heterogenous landscape of genomic differentiation shaped in part by background selection. Although recombination landscapes were conserved within all three systems, we documented a weaker negative correlation between recombination rate and genomic differentiation in the recent radiations. All divergence peaks between capuchinos, wagtails, and flycatchers were located in regions with lower-than-average recombination rates, and most divergence peaks in capuchinos and flycatchers fell in regions of exceptionally reduced recombination. Thus, co-adapted allelic combinations in these regions may have been protected early in divergence, facilitating rapid diversification. Despite largely conserved recombination landscapes, divergence peaks are specific to each focal comparison in capuchinos, suggesting that regions of elevated differentiation have not been generated by variation in recombination rate alone.